MANAJEMEN KOMPENSASI GURU HONORER PADA LEMBAGA PENDIDIKAN ISLAM MENUJU MODEL KOMPENSASI SINERGI MASLAHAH - Nuril Fitria Hidayati; Saiful Hadi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze compensation management practices for contract teachers at Islamic Educational Institutions (LPI) and to formulate a resolution model capable of addressing compensation disparities in a sustainable manner. The low level of welfare among contract teachers, stemming from the foundation's limited funding, poses a major challenge that impacts teacher motivation, professionalism, and the continuity of their service. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis, and subsequently analyzed using the Miles and Huberman interactive model, which encompasses data reduction, data display, and conclusion drawing and verification. The findings indicate that compensation disparities cannot be resolved solely by increasing salaries; rather, a more comprehensive strategy is required. This strategy involves diversifying the foundation's revenue sources, optimizing educational business units, strengthening partnerships with various stakeholders, and implementing a performance-based compensation system (merit system). The study's novelty lies in the development of the *Sinergi Maslahah* (Synergistic Public Good) Compensation Model—a model that integrates financial compensation with spiritual, psychological, and social rewards to achieve teacher welfare that is equitable, sustainable, and aligned with Islamic values.